MUTU KIMIA DAN ORGANOLEPTIK PASTA KULIT BUAH NAGA (Hylocereus polyrhizus) HASIL FERMENTASI DENGAN BERBAGAI MACAM RAGI - Hasrudin S; Rostiati Rostiati; Nur alam Nur alam (Universitas Tadulako, 2017)
This research aimed atidentifyingthe chemical quality and organoleptic properties of dragon fruit skinafter fermenting with different kinds of yeast and at determining the weight of dragon fruit rind and the typeof yeast which could produce best chemical quality and organoleptic properties. This research applied a Factorial Completely Randomized design with two factors. The first factor was the weight of red dragon fruit rind (20, 30, 40 g). The second factor was yeast types (control, bread yeast, tempeh yeast, and cassava yeast). Each experimental treatment was replicated twice, so there were 24 experimental units. The effect of the treatments was determined usinga F-test at 0.05% and if the effect significant then it would be further analyzed using an Honestly Significant Difference (HSD) test.The weight of dragon fruit rindsignificantly affected the level of anthocyanin, water content, texture, color and flavor. The weight of dragon fruit rind of 20 g resulted in better anthocyanin level while 40 g produced better pH, water content, texture, color and flavor. Keywords: Chemical quality, Dragon Fruit, Fermentation and Yeast.